Pengaruh Pembelajaran Online “Google Meet” Terhadap Minat dan Motivasi Belajar Mahamahasiswa - Hamzah Robbani; Rendika Vhalery; Arsa Rachmania (Neolectura, 2022)
With the Covid-19 pandemic, students must learn to adapt. The application of e-learning is a form of learning adjustment in the midst of the Covid-19 pandemic. This learning is aimed at students' interest in learning and motivation to learn. To achieve this quality, students must of course have a lecturer role in learning, one of which is the use of appropriate and fun learning strategies, namely Google meet. Based on this statement, this study aims to examine and determine the effect of online learning